Hepatoprotective effect of calculus bovis sativus on nonalcoholic fatty liver disease in mice by inhibiting oxidative stress and apoptosis of hepatocytes - He WX; Xu YJ; Zhang CL; Lu JL; Li J; Xiang D; Yang JY; Chang MJ; Liu D (Dove Medical Press, 2017)
Wenxi He,1 Yanjiao Xu,1 Chengliang Zhang,1 Jingli Lu,2 Juan Li,1 Dong Xiang,1 Jinyu Yang,1 Mujun Chang,3 Dong Liu1 1Department of Pharmacy, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, China; 2Department of Pharmacy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, China; 3Center for Translational Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, China Abstract: Calculus bovis (CB, niu-huang) is a high-class therapeutic drug that is often used in traditional Chinese medicine. CB helps to eliminate heat and toxic components, and prevents the accumulation of phlegm and blood stasis in the liver. In Asian countries, CB Sativus (CBS), an ideal substitute for natural CB, is presently extensively used for long-term treatment of chronic liver diseases. The present study aimed to evaluate the effects and potential mechanism(s) of action of CBS on mice with fructose-induced nonalcoholic fatty liver disease (NAFLD). The NAFLD model was established in C57BL/6 mice by exclusively feeding fluids containing 30% fructose for 8 consecutive weeks. After these 8 weeks, mice were given CBS (50 mg/kg/day or 100 mg/kg/day) for 2 consecutive weeks. Treatment with CBS reversed the fructose-induced impaired glucose tolerance. Compared with the model group, in which mice received 8 weeks of high-fructose diet and 2 weeks of 0.5% sodium carboxymethyl cellulose, CBS treatment significantly decreased the levels of fasting serum glucose, fasting insulin, triglyceride, and total cholesterol, and increased levels of high-density lipoprotein-cholesterol. CBS treatment also significantly decreased the levels of triglyceride, total cholesterol, and free fatty acid in the liver. The activity of superoxide dismutase in the liver was increased after treatment with CBS, however, levels of malondialdehyde and reactive oxygen species decreased. Histopathological examination showed that liver steatosis and injury were significantly reduced in CBS-treated mice. The expression of fatty acid synthase, nuclear factor kappa-light-chain-enhancer of activated B cells, Cysteinyl aspartate-specific proteinase-3, and synonyms B-cell leukemia/lymphoma-2 gene-associated X protein were downregulated after treatment with CBS, whereas the expression of nuclear factor erythroid-2-related factor 2 was upregulated. In conclusion, CBS treatment exerted therapeutic effects in the liver of mice with NAFLD, which may be associated with amelioration of metabolic disorders, enhanced antioxidant effects, and alleviation of apoptosis. Keywords: antioxidant, fructose, lipid metabolism, liver